Olfactory Reference Syndrome Developed After Stressful Life Events and Response to Pharmacological Treatment: Report of Four Cases - YANARTAŞ, ÖMER (KURE ILETISIM GRUBU A S, 2015)
Olfactory reference syndrome (ORS) is a disorder of thought content characterized by strong beliefs in transmitting an unpleasant body odor and disturbing other people. ORS had not been recognized in the DSM-IV as a separate diagnosis; rather, it used to be categorized under delusional disorder, somatic type (DDST). Considering recent changes in the DSM-5, the syndrome is currently listed under the section of other specified obsessive-compulsive and related disorder with the name Jikoshu-kyofu, thus still not described as a major distinct entity. We claim that a universally accepted set of diagnostic criteria is lacking, and there is a set of overlapping symptoms with various other disorders. In this paper, we discuss four patients presenting with ORS after a triggering stressful life event from the nosological and treatment perspective, focusing primarily on antipsychotic augmentation.
Keywords: olfactory reference syndrome; delusional disorder; treatment; obsessive compulsive disorder; aripiprazole; stressful life event